STRATEGI PENGELOLAAN SUMBER DAYA MANUSIA DALAM MENDUKUNG LAYANAN LITERASI DI PERPUSTAKAAN DESA SUMURUGUL - Naila, Syahnaz; Az Zahro, Fatimah (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2025)
This study aims to examine human resource management (HRM) practices in the Sumurugul Village Library, a community-based library initiated by local efforts. Village libraries play a strategic role in enhancing literacy, providing informal learning spaces, and strengthening social interaction at the community level. However, their management often faces challenges such as limited personnel, low technical competence, and insufficient continuous training support. This research adopts a qualitative approach with a case study method. Data were collected through semi-structured interviews, direct observation, and document analysis, then analyzed using data reduction, presentation, and conclusion drawing techniques. The study focused on five key managers actively involved in the library’s operations and literacy programs. The findings indicate that the library’s management structure is simple and voluntary in nature. Limitations in human resources are addressed by involving volunteers, interns, and literacy communities. Capacity development is carried out through needs-based training, webinars, and benchmarking visits. Furthermore, routine literacy programs and community participation reflect employee engagement and collaborative leadership. External support from the village government and institutional networks, although still temporary, contributes to strengthening the capacity of library managers. In conclusion, the success of HRM in the Sumurugul Village Library relies on local initiatives, intrinsic motivation, and the ability to build partnerships. These strategies enable the library to survive and function as an adaptive and sustainable literacy center despite resource constraints.